(untitled) (GUB Journal of Science and Engineering, 2022)
Differential geometry is an important aspect of current physics and the study of any planar surface. Quantum mechanics and modern science are developing with the help of differential Geometry in daily life. In this paper, we discuss two mathematical formulas named Haversine formula for spherical earth and Lambert’s formula for oblate spherical earth. These formulas are used to determine the shortest distance between two points on Earth, as well as the sine formula for determining the direction of various locations towards the North Pole. Some examples of different locations are illustrated in this literature which gives a better overview. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 8, Dec 2021 P 49-56